Quick start guide to JavaFX - DiMarzio, J. F. (McGraw-Hill Education, 2014)
"Develop and deploy interactive client applications in no time with help from this practical tutorial from Oracle Press. With a focus on working in NetBeans IDE, Quick Start Guide to JavaFX explains how to use JavaFX layouts, draw shapes, use coloring and gradient tools, load images, apply effects and transformations, include animation, and embed media. You'll also get details on using JavaFX events, subclassing existing nodes, creating custom nodes, working with WebView, and styling your applications with CSS. Designed for easy learning, the book features: Key Skills & Concepts -- Chapter-opening lists of specific skills covered in the chapter; Ask the Expert -- Q & A sections filled with bonus information and helpful tips; Try This -- Hands-on exercises that show you how to apply your skills; Notes -- Extra information related to the topic being covered; Tips -- Helpful reminders or alternate ways of doing things; Cautions -- Errors and pitfalls to avoid; Annotated Syntax -- Example code with commentary that describes the programming techniques being illustrated; Self-tests -- Chapter-ending quizzes to reinforce your skills"--